Mutual Fund Strategy: Swing for the Fences or Bat for Average - Chalmers, John; Dayani, Arash (Journal of Financial and Quantitative Analysis, 2026)
Abstract We document two distinct mutual fund strategies: “Swinging for the Fences” (SF), in which managers hold stocks with extreme style-adjusted returns on either tail of the return distribution, and “Batting for Average” (BA), in which managers seek stocks with consistently moderate performance. We provide evidence that these strategies are persistent and deliberate. Existing measures of active management and known asset-pricing factors do not explain the strategies. SF attracts more flow, particularly when funds mention specific stock holdings in shareholder reports. SF funds charge higher fees and hold riskier portfolios; yet, they fail to deliver higher risk-adjusted returns. In falsification tests, SF strategies are not present in passive funds, supporting our conclusion that SF and BA are intentional strategies.